Shortened acquisition time in simultaneous 99mTc-tetrofosmin and 123I-β-methyl-p-iodophenyl pentadecanoic acid dual-tracer imaging with cadmium–zinc–telluride detectors in patients undergoing primary coronary intervention for acute myocardial infarction. Issue 11 (November 2019) - Yamada, Yoshihiro; Nakano, Shintaro; Gatate, Yodo; Sugi, Keiki; Okano, Nanami; Muramatsu, Toshihiro; Nishimura, Shigeyuki; Kuji, Ichiei; Fukushima, Kenji; Matsunari, Ichiro
Abstract : Objective: The use of cadmium–zinc–telluride-based scanners may increase the clinical feasibility of simultaneous dual-isotope imaging. In the current study, we sought to investigate a potential acquisition time in simultaneous 99m Tc-tetrofosmin/ 123 I-β-methyl- p -iodophenyl pentadecanoic acid dual-isotope imaging using a Discovery NM/CT 670 cadmium–zinc–telluride. Methods: Simultaneous 99m Tc-tetrofosmin/ 123 I-β-methyl- p -iodophenyl pentadecanoic acid dual-isotope imaging was performed in 29 patients who had undergone primary percutaneous coronary intervention for acute myocardial infarction. Referenced images with an acquisition time of 65 s/view (16.25 min) were reframed to produce images with acquisition times of 33, 16, and 8 s/view. The values for the quantitative-gated single-photon emission computed tomography (SPECT) and the quantitative perfusion SPECT were compared. Results: The quantitative-gated SPECT values for images with 33, 16, and 8 s/views showed good consistency with those for 65 s/view (the lower 95% confidence intervals for the intraclass correlation were ≥0.80). The quantitative perfusion SPECT values for 99m Tc-tetrofosmin images with 33, 16, and 8 s/views also showed good consistency with those for 65 s/view; however, the quantitative perfusion SPECT values for 123 I-β-methyl- p -iodophenyl pentadecanoic acid images with an acquisition time of 8 s/view were not consistent with the reference acquisition time of 65 s/view. Conclusions: The quantitative-gated SPECT and quantitative perfusion SPECT values obtained from images with shorter acquisition times correlated with the values obtained from images with a reference acquisition time of 65 s/view; however, tracer-specific predisposition should be considered. These findings suggest that it is possible to reduce acquisition time when performing simultaneous 99m Tc-tetrofosmin/ 123 I-β-methyl- p -iodophenyl pentadecanoic acid dual-tracer imaging with the novel cadmium–zinc–telluride scanner. Abstract : Supplemental Digital Content is available in the text.